Galantamine Facilitates Acquisition of a Trace-Conditioned Eyeblink Response in Healthy, Young Rabbits - Simon, Barbara B. (Cold Spring Harbor Laboratory Press, 2004)
Previous work has demonstrated that drugs increasing brain concentrations of acetylcholine can enhance cognition in aging and brain-damaged organisms. The present study assessed whether galantamine (GAL), an allosteric modulator of nicotinic cholinergic receptors and weak acetylcholinesterase inhibitor, could improve acquisition and retention of an eyeblink (EB) classical conditioningtask in healthy, younganimals. We trained 24 rabbits (n = 8/group) in a 1000-msec trace Pavlovian EB conditioningparadigm in which a tone conditioned stimulus (CS) was presented for 500 msec, followed by a 500-msec trace period in which no stimuli were presented. A 100-msec corneal airpuff was the unconditioned stimulus (US). Acquisition sessions, consistingof 100 trials each, occurred daily for 10 consecutive days, followed by 3 d of extinction training. Animals were treated with one of three doses of GAL (0.0–3.0 mg/kg) prior to each session. Animals that received 3.0 mg/kg GAL showed significantly more EB conditioned responses (CRs) in fewer trainingtrials than animals receivingeither 1.5 mg/kg GAL or vehicle injections. GAL had no effect on CR performance duringextinction. Pseudoconditioningcontrol experiments, consistingof 200 explicitly unpaired tone–puff presentations indicated that GAL did not increase reactivity to the CS or US. These findings indicate that GAL may improve acquisition of moderately difficult associative learningtasks in healthy young organisms.